Use and effectiveness of palivizumab on preventing bronchiolitis due to the respiratory syncytial virus. Issue 2 (12th March 2012) - Hernanz, R.; Nogales, M.; Camaron, I.; Goitia, V.; Garcia, J.J.; Minguez, A.
Abstract : Background: In healthy infants, bronchiolitis is usually a self-limited disease. But children with some risk factor have greater frequency and severity of bronchiolitis. Purpose: To describe the use and effectiveness of palivizumab on preventing bronchiolitis due to respiratory syncytial virus (RVS) from October 2004 to April 2010. Materials and methods: Our hospital follows the Paediatric Spanish Society guidelines to determine whether the pavilizumab prophylaxis is indicated. In addition, our hospital makes a campaign to fight respiratory infections with the families of all infants. The data were taken from AS-400 software program (single dose and drug management) and Global Clinic (medical reports). Results: 170 patients were treated with palivizumab during the period. 6 of them needed hospitalisation because of bronchiolitis. In 3 of these the infection was due to RVS: 2 patients with haemodynamical unstable congenital heart disease under 24 months, and 1 premature less than 29 weeks of gestation and under 12 months old at the start of RSV bronchiolitis season risk. 367 children, who did not perform our criteria for the administration of palivizumab, were born before 35 weeks of gestation. 19 of these were hospitalised because of bronchiolitis, 7 of them due to RVS. In hospitalisation cases due to bronchiolitis by RVS the length of hospitalisation was 3, 8 and 9 days, with an age of 10, 5 and 20 months, respectively. Children who didn't receive palivizumab were hospitalised 3, 6, 6, 7, 8, 8 and 14 days (median 7), with 22, 6, 10, 2, 2, 2 and 1, 5 months old (median 2), respectively. No case needed the hospitalisation in paediatric Intensive Care Unite (ICU). The average annual cost of palivizumab treatment was 115, 087.71¤. Conclusions: If the prophylaxis with palivizumab was made in the subgroup of patients who are considered highly recommended to receive prophylaxis against RSV, it could be used with criteria of greater efficiency, more suitable with available data of clinical efficacy and pharmacoeconomic studies